Cleaner fuels for ships provide public health benefits with climate tradeoffs - Mikhail Sofiev (Nature Portfolio, 2018)
Aerosol pollution from shipping contributes to cooling but also leads to premature mortality and morbidity. Here the authors combine emission inventories, atmospheric models and health risk functions to show how cleaner marine fuels will reduce premature deaths and childhood asthma but results in larger warming.